Synthesis and crystal structure of (3E,5S,10S,13S,14S,17Z)-17-ethylidene-10,13-dimethylhexadecahydro-3H-cyclopenta[α] phenanthren-3-one O-(4-fluorobenzoyl) oxime, C28H36FNO2 - Yue Lan; Wei Peng; Ye Jiang-Hei; He Kang; Zou Juan (Zeitschrift für Kristallographie - New Crystal Structures)
C28H36FNO2, orthorhombic, P212121 (no. 19), a = 6.3277(3) Å, b = 11.9665(19) Å, c = 32.2419(19) Å, V = 2441.4(2) Å3, Z = 4, Rgt(F) = 0.0537, wRref(F2) = 0.1403, T = 273(2) K.